Republic of Kazakhstan : 2006 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
The discussions centered on the needed steps to tighten monetary conditions, curb banks' external borrowing, and reduce banks' vulnerability to a sharp deterioration in the quality of loan portfolios. Strong expansion in oil and non-oil receipts in 2005 permitted continued rapid spending growth within a sharply increasing surplus position of the overall budget. The authorities recognize that structural reforms to enhance the investment climate are critical for sustaining the non-oil sector's growth prospects. Significant gains in productivity will be required to offset the impact of the inevitable trend real exchange rate appreciation.